2002
DOI: 10.1083/jcb.200204088
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ receptor internalization into EEA1-enriched early endosomes

Abstract: Transforming growth factor (TGF)β is an important physiological regulator of cellular growth and differentiation. It activates a receptor threonine/serine kinase that phosphorylates the transcription factor Smad2, which then translocates into the nucleus to trigger specific transcriptional events. Here we show that activated type I and II TGFβ receptors internalize into endosomes containing the early endosomal protein EEA1. The extent of TGFβ-stimulated Smad2 phosphorylation, Smad2 nuclear translocation, and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
226
4
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(245 citation statements)
references
References 24 publications
12
226
4
3
Order By: Relevance
“…Previous studies have shown that TGF-β receptors undergo a rapid yet constant internalization in a ligand-dependent or -independent way [5][6][7][8][15][16][17]. The two major endocytic pathways, clathrin-mediated endocytosis and caveolae-mediated endocytosis, have been reported to independently mediate the internalization of TGF-β receptors based on indirect evidence [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that TGF-β receptors undergo a rapid yet constant internalization in a ligand-dependent or -independent way [5][6][7][8][15][16][17]. The two major endocytic pathways, clathrin-mediated endocytosis and caveolae-mediated endocytosis, have been reported to independently mediate the internalization of TGF-β receptors based on indirect evidence [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important clathrin-independent pathways is mediated by caveolae, which are flask-shaped plasma membrane invaginations marked by the presence of caveolin-1 [1,4]. Understanding the mechanism of different endocytic pathways and how these pathways are regulated is of critical importance in the study of cell signaling process, especially for transforming growth factor-β (TGF-β) sig-npg www.cell-research.com | Cell Research naling, where TGF-β receptors harness both clathrin-and caveolae-dependent pathways for internalization [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to β 2 AR and EGFR, however, TGF-β type II receptor internalization is constitutive and independent of ligand binding [13]. The clathrin-dependent endocytosis of the TGF-β type II receptor is important for TGF-β-induced Smad activation and signaling transduction [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Internalization of activated RTK from plasma membrane is a critical step of signal transduction either by terminating membrane signaling or by redirecting and sustaining signaling intracellularly. Many studies, including a recent report on VEGFR-2, suggest that receptor signaling is maintained in the endosomal compartment, which may serve as a mechanism for sustaining and amplifying membrane signaling (Urbe et al, 2000;Hayes et al, 2002;Lampugnani et al, 2006). In this study, we investigated the contribution of internalized VEGFR-2 on intracellular signaling pathways leading to NO release.…”
mentioning
confidence: 99%